2017
DOI: 10.1037/tep0000158
|View full text |Cite
|
Sign up to set email alerts
|

Advocating for advocacy: An exploratory survey on student advocacy skills and training in counseling psychology.

Abstract: Advocacy is considered a core competency within the field of counseling psychology, however more attention is needed to the training and assessment of advocacy competence for counselors-in-training. This study utilized Ratts and Ford's (2010) Advocacy Competencies Self-Assessment survey to measure self-perceived advocacy competence of master's and doctoral students within counseling (Council for Accreditation of Counseling and Related Educational Programs-accredited) and counseling psychology (American Psychol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 21 publications
1
31
0
Order By: Relevance
“…The MSJCC represent a developmental approach beginning from awareness to developing community alliances and influencing public policy (Ramirez Stege et al, 2017; Ratts et al, 2016). The framework includes four quadrants reflecting varying combinations of privileged and oppressed statuses of clients and counselors.…”
Section: Multicultural and Social Justice Counseling Competency: Concmentioning
confidence: 99%
See 4 more Smart Citations
“…The MSJCC represent a developmental approach beginning from awareness to developing community alliances and influencing public policy (Ramirez Stege et al, 2017; Ratts et al, 2016). The framework includes four quadrants reflecting varying combinations of privileged and oppressed statuses of clients and counselors.…”
Section: Multicultural and Social Justice Counseling Competency: Concmentioning
confidence: 99%
“…With respect to social justice counseling competency, counselors who trained particularly within diverse settings and communities perceived that those experiences were positively aligned with the counseling profession’s values (Hoover & Morrow, 2016) and prepared them to enact positive system‐wide change within their communities (Collins et al, 2015; Crook et al, 2015; Luu & Inman, 2018; Ramirez Stege et al, 2017; Singh et al, 2010). Furthermore, Kozan and Blustein (2018) reported that practitioners who graduated from a socially just–oriented program gained several advocacy behaviors, such as recognizing impacts of systemic factors on mental health, integrating social justice perspectives into case conceptualization and the therapeutic alliance, adopting nontraditional roles to help clients navigate multiple systems, advocating for culturally responsible practices and policies in their organizations, and addressing power dynamics and contextual issues within the profession.…”
Section: Scholarship: a Brief Reviewmentioning
confidence: 99%
See 3 more Smart Citations